Academic publishing : issues and challenges in the construction of knowledge - Hyland, Ken, 1951- (Oxford applied linguistics, 2015)
"The author discusses the impact of English as a global academic language. The growth of the assessment culture surrounding publication. The practices of knowledge construction at institutional and local levels. The emergence of Open Access and social media publishing."--Resumé vydavatele